G526(P) The experience of young people in patient and public involvement for palliative care research. (24th May 2017) - Mitchell, S; Syed, A; Seaborn, M; Samani, M; Slowther, A; Coad, J; Dale, J
Abstract : Aims: Patient and Public Involvement is an integral part of research in order to add relevance and context, and is a requirement of many research funders. The importance of evaluating the experience of PPI group members and the impact of PPI is gaining momentum. This abstract, which describes an evaluation of the experiences of young people providing PPI for a palliative care research project, is presented by the research team and three members of the PPI group. Methods: Following a PPI session with 16 young people aged between 12 and 20 years old, group members were asked to provide anonymous written feedback on any aspect of their PPI experience related to this palliative care research project. Comments were written on post-it notes using a method based on 'Tell Me…', as outlined in RCPCH and Us Recipes for Engagement. The comments were transcribed and an inductive thematic analysis conducted using NVivo. Results: Feedback was provided by all 16 young people. Two overarching themes emerged from the data: Engagement in the research. Group members want the PPI work to have an influence on the research, and for the research to have an impact. Benefits to young people included opportunity to learn both about the topic and about research more widely. ' Helps to make you feel that you are involved in helping the community ' ' Relevant interesting subject that most young people are aware of, I had experience ' ' Important as no-one wants to talk about it ! Relationship with the researcher, which allows the discussion of sensitive topics and is an ongoing process. Young people want to see the results of their PPI in the research. ' It has been conducted in a way that makes me comfortable to contribute ' The most frequently used words in the feedback included 'interesting', 'involved' and 'people'. Conclusion: PPI in palliative care research can be a fulfilling experience for young people despite the sensitive subject. The relationship with the researcher and the conduct of the PPI work are important factors. Young people report reasons to be involved as interest in the subject area, a desire to have influence on the research process and for the research to have impact.